Pemanfaatan Media Sosial Tiktok Sebagai Media Komunikasi Pemasaran Pada Akun @handmadeshoesby - Dzalila, Lizha; Amalia, Diana (Institut Agama Islam Nasional Laa Roiba Bogor, 2023)
The use of Tiktok social media has become a necessity at this time. PT. Delva Fashion uses Tiktok through the @handmadeshoesby account to carry out marketing communication activities for its products. The purpose of this study is to describe the use of Tiktok social media as a marketing communication medium on the @handmadeshoesby account. now his account has 1.2 million followers and 11.9 million likes. By using the SOME (Search, Optimize, Manage, Engage) model from Regina Lutrell. The research method used is descriptive qualitative with data collection techniques, namely interviews and documentation. The results of this study are that Handmadeshoesby utilizes Tiktok as a digital marketing communication medium by consistently creating content and live streaming.